Vegetative, physiological, nutritional and antioxidant behavior of spearmint (Mentha spicata L.) in response to different nitrogen supply in hydroponics - Chrysargyris, Antonios; Nikolaidou, Erato; Stamatakis, Aristeidis; Tzortzakis, Nikos G. (My University, 2017)
Mints are regarded as one of the most important spices throughout the world with increased demands on cultivation under controlled environment. We conducted a study to evaluate the effects of different nitrogen levels (N: 150–175–200–225–250 mg/L) on the morphological and biochemical characteristics of spearmint (Mentha spicata L.) in hydroponics. The results indicated that N levels affected plant growth and chlorophyll content, while no differences were found in chlorophyll fluorescence and stomatal conductance. Essential oil yield increased at the 225 mg/L of N application. The main constituents of the essential oil were carvone, limonene, 1,8-cineole, germacrene D and β-pinene. High N application reduced leaf micronutrients content (i.e. Mn) and therefore reduced the carvone content. Nitrogen levels did not alter total phenols and antioxidant activity (DPPH, FRAP), while flavonoids were higher in 175 and 250 mg/L comparing to the 225 mg/L of N application. The increase in ascorbate peroxidase (APX) activity in spearmint under 200 mg/L of N application was towards the oxidative stress (increased hydrogen peroxide −H2O2), providing protective action to the plant. No differences were observed in antioxidant enzymes such as superoxide dismutase (SOD) and catalase (CAT) and malondialdeyde (MDA) content. Thus, the recommendation for increase upper plant biomass and essential oil quality in spearmint is to employ 200 mg/L N.
Keywords: Antioxidants; Essential oil; Mineral fertilizer; Soilless culture; Spearmint